In Search of the Marketing Imagination: Factors Affecting the Creativity of Marketing Programs for Mature Products - Andrews, Jonlee; Smith, Daniel C. (Journal of Marketing Research, 1996)
The profitability of established products is affected greatly by the extent to which they are meaningfully differentiated from competing alternatives. Maintaining meaningful differentiation, in turn, is facilitated by ongoing development of creative marketing programs. Although marketplace observation reveals a general lack of creativity in the way established products are marketed, some product managers are able to devise creative marketing programs for their products. The authors test hypotheses concerning the effects of individual (i.e., product manager) and situational (i.e., planning process) characteristics on marketing program creativity. The findings reveal that marketing program creativity is a function of individual problem-solving inputs (e.g., knowledge of the marketing environment, diversity of experience, diversity of education), motivational factors (e.g., intrinsic motivation, risk taking), and situational factors (e.g., planning process formalization, interaction with others, time pressure).